2016
DOI: 10.1007/s10147-016-0977-x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of laparoscopic total proctocolectomy with ileal pouch–anal anastomosis and total colectomy with ileorectal anastomosis for familial adenomatous polyposis: results of a nationwide multicenter study

Abstract: Laparoscopic TPC-IPAA and TC-IRA are both feasible options-with low rates of morbidity, good functional outcomes, and excellent overall survival rates-in patients with FAP. Since the data indicate that laparoscopic TPC-IPAA and TC-IRA are feasible, they also support the recent increase in laparoscopic surgery for patients with FAP in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 41 publications
3
28
0
2
Order By: Relevance
“…All patients diagnosed as having FAP and undergoing colorectal resection in each institution between the years 2000 and 2012 were retrospectively collected and registered for the database as described previously 16, 17, 18. Patients having a previous history of colorectal resections were excluded from the database to avoid double registration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients diagnosed as having FAP and undergoing colorectal resection in each institution between the years 2000 and 2012 were retrospectively collected and registered for the database as described previously 16, 17, 18. Patients having a previous history of colorectal resections were excluded from the database to avoid double registration.…”
Section: Methodsmentioning
confidence: 99%
“…These limitations could explain inconsistent results in the previous studies, and we need evidence that focuses on patients with FAP with the use of objective criteria for assessing complications. The aim of the present study was to compare postoperative complications and short‐term outcomes after stapled and hand‐sewn IPAA for patients with FAP using multicenter data in Japan 16, 17, 18…”
Section: Introductionmentioning
confidence: 99%
“…The JSCCR multicenter study showed that temporary ileostomy was performed in 55% of patients who had undergone IPAA 25) . A systematic review of the closure of temporary ileostomy 52) revealed that closure was safe, but that 16.5% of all subjects had postoperative complications, including bowel obstruction in 7.6% (reoperation in 2.9% of all cases), anastomotic leakage in 2.0%, wound infection in 4.0%, and late complications such as incisional hernia in 1.9% and bowel obstruction in 9.4%.…”
Section: Cq4: Is Temporary Ileostomy Required In Cases Undergoing Ipamentioning
confidence: 99%
“…(1) Total proctocolectomy + permanent ileostomy (TPC) (2) Restorative proctocolectomy + ileal pouch-anal anastomosis (IPAA) (3) Total colectomy + ileorectal anastomosis (IRA) At present, IPAA is thought to be the standard surgical procedure and it is commonly performed in FAP patients [22][23][24][25] . (CQ3,CQ4)…”
Section: S11mentioning
confidence: 99%
See 1 more Smart Citation